FAKTOR YANG MEMPENGARUHI KEPATUHAN BIDAN DALAM MELAKSANAKAN PROSEDUR PERSALINAN AMAN MASA NEW NORMAL - Ainal Mardiah; Hilda Eliza (Maternal Child Health Care, 2021)
The World Health Organization (WHO) states that in 2017 worldwide, it is estimated that maternal mortality is 303,000 people or around 216/100,000 live births (KH). Mortality and morbidity in pregnant women and childbirth is a big problem in developing countries, because maternal deaths occur mainly in developing countries by 99%. Indonesia is one of the countries that is included in a developing country. Indonesia is now even included as one of the 10 largest contributors to MMR in the world, where these 10 countries account for about 59% of all deaths.mother in the world. This research is a quantitative research with a cross sectional design or approach. In this study, the sampling used is total sampling, which is taking the entire sample of the existing population (Sugiyosno, 2017) as much as 20 health workers (midwives).The results of this study indicate that there is a significant relationship between knowledge of Midwife Compliance in Implementing the New Normal Period of Safe Delivery Procedures at the 2020 Public Health Center with p value = 0.027. There is a significant relationship between attitudes towards Midwife Compliance in Implementing Safe Delivery Procedures for the New Normal Period at Puskesmas 5 Year 2020 with p value = 0.008. There is no significant relationship between education and Midwife Compliance in Implementing New Normal Safe Delivery Procedures at Puskesmas S Year 2020 with p value = 0.081. S Year 2020 with p value = 0.619.